Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jhydrol.2015.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Decadal monitoring of the Niger Inner Delta flood dynamics using MODIS optical data

Abstract: International audienceWetlands provide a vital resource to ecosystem services and associated rural livelihoods but their extent, geomorphological heterogeneity and flat topography make the representation of their hydrological functioning complex. A semi automated method exploiting 526 MODIS (Moderate Resolution Imaging Spectroradiometer) 8-day 500 m resolution images was developed to study the spatial and temporal dynamics of the annual flood across the Niger Inner Delta over the period 2000–2011. A composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
89
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 44 publications
15
89
3
2
Order By: Relevance
“…During years with high discharge (2009)(2010)(2011)(2012), it is observed that the floodplains remain inundated for extended periods of time; long after the river discharge has peaked (Figure 15). Based on the ideas of Ogilvie et al [48], the floodwater recedes from the floodplains at a slower rate than water within the channels because it is trapped in topographic depressions [48]. This can be observed in both the Zambezi and Chobe Rivers in respect to their corresponding floodplains.…”
Section: Discussionmentioning
confidence: 99%
“…During years with high discharge (2009)(2010)(2011)(2012), it is observed that the floodplains remain inundated for extended periods of time; long after the river discharge has peaked (Figure 15). Based on the ideas of Ogilvie et al [48], the floodwater recedes from the floodplains at a slower rate than water within the channels because it is trapped in topographic depressions [48]. This can be observed in both the Zambezi and Chobe Rivers in respect to their corresponding floodplains.…”
Section: Discussionmentioning
confidence: 99%
“…Water 2017, 9, 938 2 of 20 Imaging Spectroradiometer (MODIS) optical data to research the spatiotemporal dynamics of the Niger Inner Delta flood [3]. In their study, water area-stage relationships were refined by accounting for hysteresis behavior.…”
Section: Et Al Adopted Moderate Resolutionmentioning
confidence: 99%
“…Fortunately, as another feature of highly non-linear hydrologic systems of lake floodplains, research on hysteresis found between discharge levels and stages has been precise and long-standing and may provide a reference. Factors affecting stage-discharge relationships proposed by Boyer [16] are as follows: (1) the unsteadiness of river flows, which alter the slope of the water surface; (2) backwater effects that change downstream environments; (3) vegetation that affects bed roughness levels; (4) bed evolution as a result of dredging or sediment transport, etc.…”
Section: Et Al Adopted Moderate Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground-based assessments of small reservoir locations, capacities, and seasonal volumes are time-consuming to conduct because of the spatial dispersion of these reservoirs and decentralized decision making regarding reservoir investments and maintenance [12]. Many previous studies have characterized inland surface water resources using free satellite imagery, such as from Landsat [13][14][15][16][17] and the Moderate Resolution Imaging Spectroradiometer (MODIS) [18][19][20][21][22]. Where the spatial and temporal resolution are sufficiently high, remotely sensed imagery provides a practical approach to small water body mapping and monitoring [23,24].…”
Section: Introductionmentioning
confidence: 99%